The role of anti-malarial drugs in eliminating malaria. - White, N (BioMed Central, 2008)
Effective anti-malarial drug treatment reduces malaria transmission. This alone can reduce the incidence and prevalence of malaria, although the effects are greater in areas of low transmission where a greater proportion of the infectious reservoir is symptomatic and receives anti-malarial treatment. Effective treatment has greater effects on the transmission of falciparum malaria, where gametocytogenesis is delayed, compared with the other human malarias in which peak gametocytaemia and transmissibility coincides with peak asexual parasite densities. Mature Plasmodium falciparum gametocytes are more drug resistant and affected only by artemisinins and 8-aminoquinolines. The key operational question now is whether primaquine should be added to artemisinin combination treatments for the treatment of falciparum malaria to reduce further the transmissibility of the treated infection. Radical treatment with primaquine plays a key role in the eradication of vivax and ovale malaria. More evidence is needed on the safety of primaquine when administered without screening for G6PD deficiency to inform individual and mass treatment approaches in the context of malaria elimination programmes.